Max Weber's Concept of Hierocracy: A Study in the Typology of Church-State Relationships - Murvar, Vatro (Sociological analysis, 1967)
The interdisciplinary research on state-church relationship in various cultural contexts can be greatly facilitated by utilizing Weber's conceptual tools and some of his material after certain ambiguities, mainly technical and terminological, are eliminated or modified. In addition this paper presents some basic and almost universal monistic societal structures in contrast to the peculiar and fluctuating early dualism in the West. Both sets of structures seem to be very instructive for modern man in his painful search for pluralistic solutions while still haunted by the very much alive monistic value-systems of the irrevocable past.